Using Careless Speech for Careful, Well-Crafted Writing— Whatever Its Style - Peter Elbow (Journal of the Assembly for Expanded Perspectives on Learning, 2013)
Bringing the resources of speech to writing enables writers to understand and attain written eloquence.